Kejadian Berat Badan Bayi Rendah Ditinjau dari Preeklampsia - Lina Astuty (Cendekia Medika: Jurnal Stikes Al-Ma`arif Baturaja, 2020)
Research: Pre-eclampsia is a disease with signs of hypertension, edema, and proteinuria arising from pregnancy. This disease generally occurs in the third trimester of pregnancy, but can occur earlier, for example in hydatidiform mole (Wiknjosastro, 2005: 282). Preeclampsia and Eclampsia are one of the main causes of maternal mortality in Indonesia. The incidence of preeclampsia ranges from 5-15% of all pregnancies in the world. Based on the 2003 Indonesian Demographic and Health Survey (IDHS), the incidence of preeclampsia in Indonesia is estimated at 3.4–8.5%. The research method used analytical observational method through a case control approach, which is an analytical study concerning how risk factors are studied using a retrospective approach. In other words, the effect is identified now, then the risk factor is identified as having existed or occurred in the past. Research Results The results of the significance test using the Chi-Square test showed a significant relationship to the occurrence of low birth weight (LBW) in mothers with preeclampsia. This is indicated by the value of p = 0.000 which is smaller than α = 0.05, so Ho is rejected. While the results of the calculation of the Odds Ratio show that preeclampsia is one of the causes of LBW, this is indicated by the OR value of 3.028. Conclusion: There is a relationship between preeclampsia and low birth weight in dr. Soedarso Pontianak in 2018 with a probability value (ρ) = 0.000.